Teachers’ Perception about Flipped Classroom in Era of COVID-19 Pandemic - Anuradha Yadav; Manisha Sankhla; Kavita Yadav (Studies in Learning and Teaching, 2021)
The COVID-19 affects medical education by shifting classroom teaching to online mode, facing numerous challenges, particularly in developing countries, such as internet connectivity, technological issues, mode of assessment. Teachers' perspectives and various challenges affecting the e-learning system during the COVID-19 pandemic require attention to ensure effective learning, so the present study aimed to assess the above objective. After institutional ethical committee approval, a cross-sectional observational study was conducted on teachers (30 responded) of phase-I MBBS via a survey questionnaire. The qualitative data were analyzed using chi-square, with a significance level set < 0.05. The majority of teachers were female (70%) and Generation X (60 %), with an 81 % response rate. Faculty (53%) had a positive impression of online teaching but preferred face-to-face instructions (67%). With a non-significant difference (p=0.255), the majority of the teaching staff sometimes faces network and technology challenges but satisfies with online teaching and assessments. Faculty prefer traditional classroom learning and assessment as they miss student participation and feedback, with prior e-teaching training and platform privacy but recognized online mode as an alternative during COVID-19. The faculty had a positive attitude towards online teaching but lack face-to-face interaction with students. Internet access, combined with some technical difficulties, posed a challenge in providing high-quality teaching